A novel HLA‐C allele, HLA‐C*14:125. (5th February 2021) - Gualandris, Federica; Bacis, Sara; Campoli, Riccardo; Castellani, Laura; Falanga, Anna
Abstract : HLA‐C*14:125 allele is identical to HLA‐C*14:02:01:01 except for a single nonsynonymous mutation C199T.